Proses Pembentukan Peraturan Daerah Kabupaten Muna Sulawesi Tenggara - Muhammad Asrianto Zainal (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2018)
This study will discuss the process of establishing the regional regulations of Muna regency, especially the constraints. The results indicate that the establishment of regional regulations of Muna is based on DPRD Regulation Number 1/DPRD/2014 concerning the Rules of Procedure for the Muna Regency, which DPRD begins with the planning, drafting, discussion, stipulation, enactment, dissemination and evaluation of regional regulations. The formation of regulations in Muna Regency only follows procedural stages but is not substantially regulated regarding the necessity of academic manuscripts and community participation and not in accordance with Law Number 12 of 2011 concerning the Establishment of Laws and Regulations of the Minister of Home Affairs Number 1 of 2014 in legal substance, structure, and culture, such as it is not clearly regulated the necessity of making academic texts; lack of human resources; lack of community participation, universities and other parties in the process of establishing regional regulations.